La incidencia de las pausas activas en la salud postural dorsal posterior de los trabajadores Universitarios - Fonseca Parra, Cesar Augusto (2018)
The present investigation "The influence of the active pauses in the posterior dorsal postural health of the university workers of the UNACH campus the painful one", we determine the influence of the extra-physical activity in the dorsal posture of the administrative personnel, taking as a population the university workers, with a final sample of 20 people, including 14 women and 6 men who participated in active breaks. The investigative work is of a quasi-experimental type of qualitative nature where a pre-post intervention evaluation was carried out using the Posturograma test. An instrument endorsed in 2010 by Martha Vélez is an effective ergonomic instrument in detecting affections and shovels postures due to work, after finishing with the intervention of the active pauses which lasted 8 weeks, We verified the incidence of active breaks in non-work work by determining the relationship of the variables obtained and showing benefits in physical change and of the UNACH workers.